How Far Can Tourism Go? Residents' Attitudes toward Tourism Development in Yogyakarta City, Indonesia - Mohamad Yusuf (Faculty of Geography, Universitas Gadjah Mada, 2020)
In the last 10 years, tourism has been rapidly growing in Yogyakarta. Studies show that tourism development in Yogyakarta has led to irritated feelings among local residents. This study aims to measure residents' attitudes toward tourism development in Yogyakarta by using validated measurement properties with a scale that measures residents' attitudes toward sustainable tourism development (SUS-TAS). The instrument was distributed to 1,687 local residents living in three main tourist destinations in Yogyakarta. Confirmatory factor analysis was conducted to measure the validity and internal reliability of each variable. Descriptive quantitative analysis was also conducted to investigate the level of agreement among residents to each variable. Findings support the seven dimensions in the SUS-TAS scale. Perceived social cost and community participation are the variables with the lowest level of agreement among the variables. Results also confirm underlying tourism development problems in Yogyakarta.